Erlangen Score as a tool to predict progression from mild cognitive impairment to dementia in Alzheimer's disease - Baldeiras, I (2019)
BACKGROUND: The previously described and validated Erlangen Score (ES) algorithm enables interpretation of the cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD), ordering them on an ordinal scale: from neurochemically normal (ES = 0) through improbable AD (ES = 1), possible AD (ES = 2 or 3), to probable AD (ES = 4). Here we assess the accuracy of the ES in predicting hazards of progression from the mild cognitive impairment (MCI) stage of AD to the dementia stage of the disease (Alzheimer's disease dementia (ADD)) in a novel, single-center cohort. METHODS: Baseline CSF biomarkers (amyloid beta (Aβ) 1-42, Aβ42/40, Tau, and pTau181), interpreted according to the ES, were used to estimate time to progression from the MCI stage of AD to ADD, conditional on age, gender, APOE ε4 genotype, and Mini Mental State Examination score in 144 MCI subjects, using the Extended Cox Model; the subjects were followed-up until they developed dementia or until they had been cognitively stable for at least 2 years. In addition, ES distributions were studied in 168 ADD cases and 66 neurologic controls. Further, we stratified MCI patients into those who progressed to ADD faster (within 3 years, n = 47) and those who progressed slower (n = 74). RESULTS: The distributions of the ES categories across the four diagnostic groups (Controls, MCI-Stable, MCI-AD, and ADD) were highly significantly different (Kruskal-Wallis χ2(df = 3) = 151.4, p < 0.001), with significant contrasts between each pair (p < 0.005), except between the ADD and the MCI-AD groups (p = 1.0). MCI patients with ES = 2 or 3 had 6-8 times higher hazards to progress to ADD compared to patients with ES = 0 or 1 in the first 3 follow-up years, and then their hazards decreased to those of the group with ES = 0 or 1. Patients with ES = 4 had hazards 8-12 times higher compared to the ES = 0 or 1 group. Faster progressors with ES = 2 or 3 had, in comparison to slower progressors, significantly lower Aβ1-42, Aβ1-40, and Aβ42/40, but comparable Tau and pTau181. A highly significant difference of the ES distributions between these two groups was observed (p < 0.001). CONCLUSIONS: Our current results reconfirm and extend the conclusions of the previously published report that the Erlangen Score is a useful tool facilitating interpretation of a complex pattern of the CSF AD biomarkers.